2008
DOI: 10.1007/s00198-007-0545-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tibolone and raloxifene on bone mineral density in osteopenic postmenopausal women

Abstract: Tibolone 1.25 mg/day for 2 years prevents postmenopausal bone loss in older women and results in a larger increase of BMD both at the lumbar spine and hip than raloxifene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
1
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 34 publications
1
16
1
3
Order By: Relevance
“…According to this study, the decrease in CTX I is the highest in the sixth and twelfth month, but since our study relates to a shorter term, we are unable to compare these values at these two points in time. However, what we can conclude by comparing our results with the results of this study is that tibolone has a major effect on the change in CTX I, and that since it is about women in early menopause, this rate of decline of the bone marker in our study is higher than in the study of Delmas et al (14). Tibolone therapy, as a form of antiresorptive treatment, distinctly reduces the level of bone resorption in postmenopausal women with osteopenia, while its effect on bone formation is less pronounced.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…According to this study, the decrease in CTX I is the highest in the sixth and twelfth month, but since our study relates to a shorter term, we are unable to compare these values at these two points in time. However, what we can conclude by comparing our results with the results of this study is that tibolone has a major effect on the change in CTX I, and that since it is about women in early menopause, this rate of decline of the bone marker in our study is higher than in the study of Delmas et al (14). Tibolone therapy, as a form of antiresorptive treatment, distinctly reduces the level of bone resorption in postmenopausal women with osteopenia, while its effect on bone formation is less pronounced.…”
Section: Discussioncontrasting
confidence: 59%
“…The difference between our study and the study of the author named lies primarily in the fact that in the mentioned study the women were older and on average in postmeno pause for 17 years, which resulted in a major fall in the T score compared to our patients. Comparison of other characteristics of our patients and the ones from the study of Delmas et al (14) revealed that the patients did not differ significantly regarding other cha racte ris tics. According to this study, the decrease in CTX I is the highest in the sixth and twelfth month, but since our study relates to a shorter term, we are unable to compare these values at these two points in time.…”
Section: Discussionsupporting
confidence: 49%
“…Alguns trabalhos preconizam (20,26) ou seria ainda melhor (17) . A dose de tibolona utilizada no atual experimento foi considerada alta em comparação com a habitualmente empregada em humanos.…”
Section: Discussionunclassified
“…Sabe-se que a tibolona preserva a massa óssea de forma semelhante ao estrogênio pela inibição do aumento da reabsorção óssea induzida por ooforectomia, no entanto, se a redução da remodelagem óssea for excessiva, pode comprometer a competência biomecânica do material ósseo em tratamentos a longo prazo (18) . É relevante considerar desde já a afirmação recém-exposta juntamente com os resultados adquiridos nesta pesquisa, além do fato de que doses inferiores já vêm sendo preconizadas (17) . Entende-se a importância do estudo sobre os efeitos de um fármaco amplamente utilizado por mulheres na pós-menopausa, cujas consequências de uma possível administração inadequada podem prejudicar todo o contexto clínico, social e psicológico dessas mulheres.…”
Section: Discussionunclassified
“…Tibolone has shown to improve bone mineral density by 3-9% in few small studies. In a recent trial, Tibolone was found to be more efficacious when compared to raloxefene in increasing the spine bone mineral density (BMD) [18]. However, the larger LIFT trial, a trial designed to examine the effect of tibolone on vertebral fracture in postmenopausal women, did report a reduction in risk with tibolone.…”
mentioning
confidence: 99%